Knowledge About Dental Caries in Grade VI A Students of SDN Wonokromo 1 Surabaya - Imam Sarwo Edi; Silvia Prasetyowati; Isnanto; Lorenza Vrinda Marcelyan; Anshad Ansari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
According to WHO, 12 year old children are Global Monitoring of Dental Caries, because all permanent teeth of 12 year old children have grown except for the third molars. The problem in this study is the DMF-T figure in class VI A students at SDN Wonokromo 1 Surabaya in 2022, the DMF-T results were 3.7, which is included in the moderate category. The study aims to determine the knowledge of class VI A students of SDN Wonokromo 1 about dental caries in Wonokromo District, Surabaya City. The type of research used is descriptive research, with 30 students as respondents. The data collection method uses a questionnaire method. Data analysis techniques by calculating the average answer from respondents. The results of this study show that students' knowledge about the definition and causes of dental caries is included in the good criteria, knowledge about the effects of dental caries is included in the good criteria, knowledge about how to prevent dental caries is included in the good criteria, and knowledge about dental caries treatment is included in the moderate criteria, so it can be concluded that the knowledge of class VI A students of SDN Wonokromo 1 Surabaya is included in the good criteria.